EFFECTIVENESS OF DISTRACTION AND ORTHOGNATHIC INTERVENTION IN THE TREATMENT OF MESIAL OCCLUSION IN PATIENTS WITH MAXILLARY UNDERDEVELOPMENT - І. Скрипник; С. Шнайдер; О. Дєньга; Ж. Новікова; С. Рачинський; О. Демид (Неонатологія, хірургія та перинатальна медицина)
Mesial occlusion is a complex orthodontic pathology that adversely affects facial aesthetics, masticatory function, and patient quality of life, making timely treatment critical. One of the modern methods of correction is distraction osteogenesis, which allows gradual expansion of bone structures while minimizing the risk of relapse. The choice of treatment is based on the patient's clinical presentation, with distraction being a priority in cases where traditional surgery is contraindicated.